Macrorestriction analysis and antimicrobial susceptibility profiling of Salmonella enterica at a University Teaching Hospital, Kuala Lumpur - Tiong, V.; Thong, Kwai Lin; Yusof, M.Y.M.; Hanifah, Y.A.; Sam, J.I.; Hassan, H. (2010)
The genetic diversity and antimicrobial resistance rates of clinical Salmonella isolates (2007-2008) at the University of Malaya Medical Centre, Kuala Lumpur, were investigated and the genetic diversity of the isolates was determined by pulsed-field gel electrophoresis (PFGE) and repetitive extragenic palindromic (REP)-PCR. XbaI-PFGE analysis generated 57 profiles (Dice coefficient, F=0.08-1.00), whereas REP-PCR using the REP primer generated only 35 (F=0.34-1.00). PFGE was therefore the more discriminative and reproducible method for assessing the genetic diversity of salmonellae. The antibiograms of 78 Salmonella isolates were assessed against 19 antimicrobials using the disk diffusion method. Twenty serotypes were identified, with the most common being S. Enteritidis (18%) followed by S. Typhimurium (14%), S. Paratyphi B var Java (9%), S. Weltevreden (9%), and S. Corvallis (9%). A total of 38 resistant profiles were defined, with 53.8% of the isolates being resistant to three or more antimicrobials. The highest resistance rates were observed for cephalothin (55.1%), tetracycline (47.4%), and nalidixic acid (35.9%). The presence of multidrug-resistant Salmonella strains is a cause for concern as it may limit the treatment of severe salmonellosis. One multidrug-resistant S. Enteritidis strain was a putative extended-spectrum beta-lactamase producer, based on a double disk diffusion analysis, and was resistant to ceftriaxone (MIC>32 microg/mL). The data generated by this study will contribute towards epidemiological monitoring and investigations of Salmonella infections in Malaysia.